Secularism, assimilation and the crisis of multiculturalism : French modernist legacies - Jansen, Yolande (IMISCOE research., 2013)
Jansen's book shows how even the most sophisticated academic views defending secularism and assimilation remain rooted in unexamined 'modernist dichotomies' inherited from French (and to some extent, European) modernism -- Publisher's description.